2008
DOI: 10.1681/asn.2007090982
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 Signaling Mediates Inflammation and Tissue Injury in Nephrotoxicity

Abstract: The molecular mechanisms of acute kidney injury (AKI) remain unclear. Toll-like receptors (TLRs), widely expressed on leukocytes and kidney epithelial cells, regulate innate and adaptive immune responses. The present study examined the role of TLR signaling in cisplatin-induced AKI. Cisplatin-treated wildtype mice had significantly more renal dysfunction, histologic damage, and leukocytes infiltrating the kidney than similarly treated mice with a targeted deletion of TLR4 [Tlr4(Ϫ/Ϫ)]. Levels of cytokines in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
256
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(280 citation statements)
references
References 61 publications
(81 reference statements)
11
256
1
2
Order By: Relevance
“…TLR4 signalling also plays an important role in the development of various kidney diseases, yet the role of TLR4 in diabetic glomerulopathy or hyperlipidaemiainduced kidney damage remains to be elucidated [8][9][10][11][12][13]. Recently, Burkhardt et al and Bouma et al reported that serum S100A8/A9 complex concentrations were elevated in patients with diabetes [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR4 signalling also plays an important role in the development of various kidney diseases, yet the role of TLR4 in diabetic glomerulopathy or hyperlipidaemiainduced kidney damage remains to be elucidated [8][9][10][11][12][13]. Recently, Burkhardt et al and Bouma et al reported that serum S100A8/A9 complex concentrations were elevated in patients with diabetes [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…TLR4, one of the best-characterised TLRs, binds with lipopolysaccharide from Gram-negative bacterial cell walls and with several endogenous ligands [7]. TLR4 also plays an important role in various kidney disorders, such as glomerulonephritis, renal ischaemia and diabetic tubular inflammation [8][9][10][11][12][13], but the role of TLR4 in diabetic glomerular injury and hyperlipidaemia-induced kidney damage remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…TLR-4 appears to play a key inflammatory role in AKI. 29 There is a significant up-regulation of monocytic TLR-2 and TLR-4 expression in septic patients when compared with healthy individuals. 30,31 In addition, the expression of TLR-2 and TLR-4 in hepatic and splenic macrophages is significantly increased in mice with experimental peritonitis induced by cecal ligation and puncture.…”
mentioning
confidence: 99%
“…This arm of the immune system involves several distinct families of soluble and cellular receptors that activate proinflammatory signaling pathways ( Figure 1). These cellular receptors include Toll-like receptors (TLRs), [1][2][3][4] retinoic acid-induced gene-like receptors, nucleotide-binding domain-leucine-rich repeat (or NOD-like receptors; NLRs), scavenger receptors, and C-type lectins that are activated by various bacterial and viral pathogen-associated molecular patterns (PAMPs), resulting the engagement of nuclear factor-B (NF-B), 5 IFN regulatory factors, and mitogen-activated protein kinase signaling pathways modulating proinflammatory and type I IFN genes.…”
mentioning
confidence: 99%